Oxidatively Active Plant Phenolics Detected by UHPLC-DAD-MS after Enzymatic and Alkaline Oxidation - Jorma Kim; Maija Pälijärvi; Maarit Karonen; Juha-Pekka Salminen (SPRINGER, 2022)
We developed a combination of methods to estimate the alkaline oxidative conditions of the midgut of insect larvae and to reveal the alkaline and enzymatic oxidative activities for individual phenolic compounds present in the larval host plants. First, we monitored the in vitro isomerization of 5-O-caffeoylquinic acid (5-CQA) into 3-CQA, 4-CQA and 5-CQA at pH 9.0-11.0. Then we calculated the isomer ratios of 3-CQA, 4-CQA and 5-CQA from the frass of eight species of insect herbivores fed on foliage containing 5-CQA. The isomer ratios suggested that the midgut pH of these larvae ranged from 9.4 to around 10.1. Second, we developed an in situ enzymatic oxidation method that enabled oxidation of phenolics in a frozen plant sample at 30 A degrees C by species- and tissue-specific enzymes. Then we measured the alkaline and enzymatic oxidative activities of the individual phenolics in 20 plant species by quantifying the proportion of the compound concentration lost due to the auto-oxidation of a plant extract at pH 10 and due to the enzymatic oxidation of the frozen plant sample at 30 A degrees C. Our results showed that both of the oxidative activity types depended primarily on the type of phenolic compound, but the enzymatic oxidative activity depended also on the plant species and tissue type. This combination of methods offers an approach to characterize a wide array of phenolics that are susceptible to oxidation by the plant enzymes and/or by the alkaline conditions estimated to prevail in the insect midgut. We propose that these kinds of compound-specific results could guide future studies on specific plant-herbivore interactions to focus on the phenolics that are likely to be active rather than inactive plant phenolics.